Analysis of anchor rod failure in a guyed transmission tower: Influence of microstructures and corrosion mechanisms. (March 2021) - Matos, T.S.; Portella, K.F.; Henke, S.L.; Bragança, M.O.G.P.; Galvão, M.P.; Dias, B.G.; Lagoeiro, L.; Almeida, L.M.
Graphical abstract: Highlights: Analysis of premature anchor rod failure in guyed transmission towers. Deformations in steel microstructure were identified by EBSD analysis. High chloride content found in the rust. Increase of chloride and sulfate content in the soil adhered to corroded anchor rod. Iron oxyhydroxide (FeOOH) formations were the key to premature anchor rod failure. Abstract: The mechanical rupture of buried structural components, such as the anchor rods of guyed transmission towers, poses a significant problem in electrical and mechanical engineering. In this work, joint evaluation of anchor rods microstructures, corrosion products, and environmental analysis of corroded anchor rods in a guyed tower was conducted. Microstructural metal analysis, electron microscopy scanning, and backscattered electron diffraction (type FEG-SEM/EBSD) were used to determine the disorientation of the crystalline structure (misorientation angle <5°) and elongated grains with sizes around 2–10 µm. Predominant crystallographic planes (0 0 1) and (1 1 1) were found to be more susceptible to corrosion than (1 0 1). Researchers also observed accumulations of chloride ions in concentrations of up to 10.2% in corrosion products, and in the soil surrounding the anchor rod, chloride and sulfate ions were found in concentrations of up to 5.15% and 2.33%, respectively.